Hubungan Tingkat Iq Dengan Motivasi Mahasiswa Fipp Unima - Jofie Hilda Mandang (Jurnal Ilmiah Wahana Pendidikan, 2023)
Learning motivation is a problem that is often discussed in the world of education, including in higher education, where students are required to have high motivation in learning, but not all students can do it effectively. One of the factors that influence it is intelligence or intelligence, because IQ is a person's thinking capacity that determines his way of thinking in solving various problems faced. This research is to find out the relationship between intelligence level (IQ) and student learning motivation. Using a quantitative approach with correlational methods. Members of the sample 43 students who were taken randomly. Data collection techniques for IQ test CFIT scale 3, and motivation to learn using a questionnaire. Hypotensive testing using the product moment correlation analysis technique, the results obtained rXY count = 0.77 at a significance of 0.05 dk 43 price rxytable = 0.301. It turns out that r count is greater than r table or 0.458 > 0.301. This means that Ha is accepted and Ho is rejected. The determinant degree between intelligence and student learning motivation is r2 = 0.59. This shows that 59% of the variance of student learning motivation (Y) is determined by the intelligence variable, while the remaining 41% is determined by other factors not examined in this study. It can be concluded that the intelligence level (IQ) has a positive and very significant relationship with student learning motivation.